Enjoying extinction: philanthrocapitalism, jouissance, and 'excessive environmentourism' in the South African rhino poaching crisis - Stasja Koot (Journal of Political Ecology, 2021)
From 2007 to 2015, rhino poaching grew rapidly in and around Kruger National Park, South Africa. And though poaching numbers have declined since then, the 'poaching crisis' and its consequences continue to influence rhetoric and practice in the area, including continuing public outcries that the rhino is close to extinction. This discourse of extinction is also prevalent among the luxurious tourist lodges on private nature reserves of the Greater Kruger Area that attract wealthy tourists. In response, some lodges started initiatives in which tourists can join the fight against rhino poaching. These tourist activities share important similarities with 'philanthrocapitalism',in which wealthy philanthropists address social and environmental challenges drawing on the same business principles that made them successful. Based on research on the tourism industry, I explore the political ecology of such high-end, 'environmentourist' activities. I argue that philanthropic environmental tourist activities are based on a reductionist articulation of the rhino poaching crisis. They de-politicize it from its socio-economic and historical context and are 'excessive', in that they produce and legitimize exorbitant forms of privatized, luxurious tourism and consumerism as a solution for social and environmental crises. Moreover,such 'excessive environmentourism' allows wealthy tourists to enjoy 'doing good'in a very specific way, best captured by the term 'jouissance.' Jouissance is a particular type of ambivalent enjoyment that includes fascination with dark and horrific elements (i.e. poached rhinos and the idea that these animals are at the brink of extinction). I conclude that jouissance functions as a core motivation for wealthy tourists to engage in touristic experiences precisely because it enables them to believe they can overcome the dark sides of their own excesses ironically by 'doing good', grounded in excessive consumption.